How do students solve critical thinking tasks in trigonometry? A qualitative analysis of critical thinking skills - Aridanthy, Vanya; Kusumah, Yaya S.; Dahlan, Jarnawi Ahmad; Prabawanto, Sufyani; Melati, Catur Yustika (Universitas Islam Negeri Raden Intan Lampung, 2026)
Critical thinking skills are crucial for students to analyze and solve problems effectively, yet many still struggle in apply them comprehensively. This study aimed to examine students' critical thinking skills using a qualitative descriptive approach. The study used an essay-based assessment developed based on the framework of Perkins and Susilo et al., which includes four main indicators: clarification, judgment, inference, and strategy development. The findings indicated that students demonstrated partial critical thinking skills; most could analyze or clarify problems, while some could present problems with reasoning or examples and draw compelling conclusions. However, many students still struggled to develop effective problem-solving strategies. These results imply the need for improved instruction that places greater emphasis on strengthening problem-solving skills to enhance students' overall critical thinking skills.